Wind turbine condition monitoring and reliability analysis by SCADA information - Wenxian Yang; Jiesheng Jiang (2011 Second International Conference on Mechanic Automation and Control Engineering, 2011)
As the deployment of onshore wind turbines becomes established and with an increasing deployment of offshore wind turbines, to ensure a high reliability and availability of these machines has become the focus of interest within the academic and industrial communities. One of the approaches to meet this requirement is to develop a Reliability Centered Maintenance (RCM) strategy with the aid of an advanced condition monitoring and reliability prediction system. The aim of this paper is to describe the basic idea of how wind farm Supervisory Control and Data Acquisition (SCADA) system contributes to establishing such a strategy. Examples have been given in the paper for providing a clear explanation of the opinions.